A highly hydrophobic cosmetic-grade mica material and preparation method thereof
By using a variety of silane coupling agents on the surface of mica, a highly hydrophobic cosmetic-grade mica material is formed, which solves the problem of insufficient hydrophobicity of existing mica materials and achieves better makeup durability and waterproof and sweat-proof effects. , and reduces production costs.
Patent Information
- Application Number
- CN202410158076.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-02
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-02-02
AI Technical Summary
It is difficult for existing mica materials to achieve complete hydrophobicity in cosmetics, which limits its application in cosmetic products, and the modification effect of existing silane coupling agents needs to be further improved.
N,N-dimethylformamide, mica, γ-aminopropyltriethoxysilane (KH550), n-octyltriethoxysilane (OTES) and/or dodecyltriethoxysilane (DTES) is used as a raw material to form highly hydrophobic cosmetic grade mica materials through specific chemical reactions and temperature control, and a variety of silane coupling agents work together to improve the hydrophobic properties of mica.
It significantly improves the hydrophobic contact angle of mica to reach 131°, enhances its breathability, dispersion, softness and anti-stickness, extends the durability of makeup, waterproof and sweat-proof effects, reduces the use of silane coupling agent, and Simple process and environmentally friendly.
Smart Images

Figure CN118078655B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fine chemicals and composite materials, and particularly relates to a highly hydrophobic cosmetic-grade mica material and a preparation method thereof. Background Art
[0002] Powder raw materials are increasingly used in cosmetics. The powders used in the cosmetics industry include three categories: inorganic powders, organic powders, and natural powders. Inorganic powders have great advantages in actual production applications due to their chemical inertness, simple synthesis, low price, and easy availability. Inorganic powders generally play the role of covering, smoothness, oil absorption, waterproofing, and sun protection in cosmetics. The more commonly used inorganic powders are mainly silica, talc, mica, etc. Among them, mica has strong adhesion and moderate gloss and softness. It is almost transparent when applied to the skin and will not turn white. It is extremely widely used in makeup.
[0003] The surface of natural mica contains hydrophilic hydroxyl groups and other structures, which are easy to agglomerate, have poor compatibility with polymers, and are difficult to disperse in organic media; its non-waterproof and non-sweatproof properties will make the makeup not last long when used in cosmetics. Therefore, the development of surface treatment technology can improve this phenomenon in response to the special needs of various cosmetic products. Through surface treatment, the properties of mica can be improved, such as water resistance, lipophilicity, silky skin feel, excellent compatibility, stability of raw materials, and improved compatibility with active ingredients, which increases the added value of mica and can meet the needs of more consumers.
[0004] There are many factors that affect the surface modification effect of mica, such as the type of surface modifier, the amount of modifier, the modification temperature, the modification time, the modification method, etc. However, the type of surface modifier plays a decisive role in the modification effect. At present, the commonly used surface modifiers for fillers such as quartz powder, kaolin, and mica containing more silicic acid components include coupling agents, silicone oils, surfactants, etc. Silane coupling agent is a representative coupling agent. It has a good coupling effect on inorganic particles with hydroxyl groups on the surface, has a strong degree of chemical bonding with the mica surface, and has a good modification effect on mica.
[0005] For example, γ-aminopropyltriethoxysilane (KH550) is an amino silane coupling agent with rich nitrogen and oxygen-containing groups, and is often used for hydrophobic modification of sericite. In recent years, however, the modification effect of mica using KH550 by existing methods needs to be improved, and the application field of KH550 needs to be expanded. Although silane coupling agents can form stable chemical bonds with the hydroxyl groups on the surface of mica, existing reports show that mica modified with a single silane coupling agent cannot achieve complete hydrophobicity, which limits its practical application in cosmetic systems (Wang Xinlei. Research on the preparation of modified sericite and biomass carbon quantum dots using silane coupling agent (KH550) [D]. Jilin University, 2023).
[0006] Chinese invention patent CN109021619A discloses a method for preparing a hydrophobic and lipophilic cochineal pearlescent pigment, wherein the hydroxyl groups in the cochineal acid molecules are first esterified to prepare an oil-soluble cochineal pigment, and then the mica substrate treated with a silane coupling agent is colored with the oil-soluble cochineal pigment to prepare a novel pearlescent pigment. The hydrophobic and lipophilic surface of the pearlescent pigment is more easily wetted by an oily solvent, which can improve its dispersion in environments such as oily coatings, oily inks, and oily cosmetics. However, the invention does not specifically specify what type of silane coupling agent-modified mica has the effect of significantly improving hydrophobicity.
[0007] Even if two coupling agents or silane coupling agents with good performance are used in combination with silicone oil, there is a certain hydrophobicity improvement effect, but the corresponding hydrophobic contact angle improvement is still not good. For example, Chinese invention patent CN107337943A has opened a method for organic coating of mica powder for cosmetics, comprising the following steps: using dimethyl silicone oil and silane coupling agent to mix with a suspension made of mica powder for wet grinding, hydrophobic treatment of mica powder, then under weak acid conditions, adding a cationic surfactant for reprocessing, and then alcohol precipitation to remove impurities, through nano titanium dioxide, the obtained mica powder feels smooth, has good gloss, high transparency, and obvious pearlescent effect, effectively avoiding the defects of difficult cleaning and easy residue in the prior art, and has the characteristics of water resistance, durability, easy cleaning, and no residue. However, the hydrophobic effect of mica powder has not been significantly improved.
[0008] Therefore, it is urgent to explore more effective methods for hydrophobic modification of mica surface, significantly reduce the amount of silane coupling agent used, and improve the hydrophobic properties of mica. A method of using a specific type of coupling agent mixture, in combination with a specific ratio and dosage, to significantly improve the hydrophobic contact angle of mica is studied. The mica material has good affinity with the skin, improves its air permeability and hydrophobicity, dispersibility, softness, and anti-stickiness, greatly enhances the waterproof and sweat-proof properties of cosmetics, and makes the makeup more durable. Summary of the invention
[0009] The present invention aims at the problems existing in the prior art and provides a highly hydrophobic cosmetic grade mica material and a preparation method thereof, specifically: using N,N-dimethylformamide (DMF), mica (Mica), γ-aminopropyl triethoxysilane (KH550), n-octyl triethoxysilane (OTES) and / or dodecyl triethoxysilane (DTES) as raw materials, under the regulation of certain temperature and water, a highly hydrophobic cosmetic grade mica material is obtained through chemical reaction. The material has good affinity with the skin, good air permeability and hydrophobicity, dispersibility, softness, and anti-stickiness, and can be used as an inorganic powder raw material for makeup such as pressed powder, loose powder, and liquid foundation, greatly enhancing the waterproof and sweat-proof properties of makeup products and making the makeup more durable.
[0010] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0011] First, the present invention provides a method for preparing a highly hydrophobic cosmetic-grade mica material, comprising the steps of:
[0012] (1) dispersing mica in DMF to obtain a mica-containing slurry A;
[0013] (2) mixing the silane coupling agent mixture containing KH550 with slurry A until uniform, to obtain slurry B;
[0014] (3) condensing and reflux heating the slurry B;
[0015] (4) mixing water with the slurry obtained in step (3) to obtain slurry C;
[0016] (5) condensing and reflux-heating slurry C to obtain slurry D;
[0017] (6) Slurry D is filtered, and the obtained precipitate is washed and dried to obtain a highly hydrophobic cosmetic grade mica material.
[0018] Preferably, in step (1), the solid-to-liquid ratio of mica to DMF is 8-12:30-45 g / mL.
[0019] Further preferably, the solid-to-liquid ratio of mica to DMF is 10:35 g / mL.
[0020] Preferably, in step (2), the silane coupling agent mixture containing KH550 further comprises OTES and / or DTES.
[0021] Preferably, the silane coupling agent mixture containing KH550 is a mixture of KH550 and OTES; or a mixture of KH550, OTES and DTES.
[0022] Further preferably, when the silane coupling agent mixture containing KH550 is a mixture of KH550 and OTES, the volume ratio of KH550:OTES is 0.5-1:0.5-2; when the silane coupling agent mixture containing KH550 is a mixture of KH550, OTES and DTES, the volume ratio of KH550:OTES+DTES is 0.5-1:0.5-2;
[0023] More preferably, when the silane coupling agent mixture containing KH550 is a mixture of KH550 and OTES, the volume ratio of KH550:OTES is 1:2; when the silane coupling agent mixture containing KH550 is a mixture of KH550, OTES and DTES, the volume ratio of KH550:OTES+DTES is 1:2;
[0024] More preferably, the volume ratio of KH550:OTES:DTES is 1:1:1.
[0025] Preferably, in step (2), in the silane coupling agent mixture, the ratio of the mass of mica to the volume of the silane coupling agent mixture is 10:0.705-7.5 g / mL.
[0026] Further preferably, the ratio of the mass of mica to the volume of the silane coupling agent mixture is 10:0.705-5 g / mL.
[0027] More preferably, the ratio of the mass of mica to the volume of the silane coupling agent mixture is 10: 0.705-1.875 g / mL.
[0028] Preferably, in step (3), the condensation reflux heating is reflux heating at 110-130° C. for 1-2 h.
[0029] Further preferably, the condensation reflux heating is reflux heating at 120° C. for 1-1.5 h.
[0030] Preferably, in step (4), the volume ratio of water to DMF is 5-40:35.
[0031] Further preferably, the volume ratio of water to DMF is 12.5-14:35.
[0032] More preferably, the volume ratio of water to DMF is 12.5:35.
[0033] Preferably, in step (5), the condensation reflux heating is reflux heating at 110-130° C. for 1-2 h.
[0034] Further preferably, the condensation reflux heating is reflux heating at 120° C. for 1-1.5 h.
[0035] Preferably, step (6) is specifically as follows: filtering the slurry D to obtain a white precipitate, washing it with anhydrous ethanol and water for 2-3 times respectively, and drying it at 100-110° C. for 3-5 hours to obtain a highly hydrophobic cosmetic grade mica material.
[0036] Then, the present invention provides a highly hydrophobic cosmetic-grade mica material prepared by the above preparation method.
[0037] Furthermore, the present invention provides the use of a silane coupling agent mixture containing KH550 in the preparation of a highly hydrophobic cosmetic-grade mica material.
[0038] The silane coupling agent mixture containing KH550 further includes components OTES and / or DTES;
[0039] Preferably, the silane coupling agent mixture containing KH550 is a mixture of KH550 and OTES; or a mixture of KH550, OTES and DTES;
[0040] Further preferably, when the silane coupling agent mixture containing KH550 is a mixture of KH550 and OTES, the volume ratio of KH550:OTES is 0.5-1:0.5-2; when the silane coupling agent mixture containing KH550 is a mixture of KH550, OTES and DTES, the volume ratio of KH550:OTES+DTES is 0.5-1:0.5-2;
[0041] More preferably, when the silane coupling agent mixture containing KH550 is a mixture of KH550 and OTES, the volume ratio of KH550:OTES is 1:2; when the silane coupling agent mixture containing KH550 is a mixture of KH550, OTES and DTES, the volume ratio of KH550:OTES+DTES is 1:2;
[0042] More preferably, the volume ratio of KH550:OTES:DTES is 1:1:1.
[0043] Finally, the present invention provides application of the above-mentioned highly hydrophobic cosmetic-grade mica material in the preparation of cosmetics.
[0044] Preferably, the cosmetics include but are not limited to cakes, loose powders, and liquid foundation.
[0045] The mica described in the present invention is a layered silicate mineral, and its unit crystal structure consists of two silicon-oxygen tetrahedrons and one octahedron, and the octahedron is located between the two tetrahedrons. The cations Al, Mg, etc. located in the octahedron are connected to the two O in the silicon-oxygen tetrahedron layer. 2- and an OH at the center of the hexagon -Phase coordination, forming a hydroxide aluminum layer or a hydroxide magnesium layer. The Si-O-group is exposed on the surface of the crushed mica due to the break of the silicon-oxygen bond Si-O-Si, which forms Si-OH under the action of water and exposes active groups such as Al-OH, so it can be surface modified. Silane coupling agent is the most commonly used modifier in mica surface modification. It is an organic silicon compound with two different reactive groups in the molecule. Its chemical structure can generally be expressed by the general formula R-Si-X 3 It is represented by; X is a hydrolyzable group, usually an alkoxy group, etc. The hydrolyzed group can chemically combine with inorganic materials or adsorb on the surface of materials, thereby improving the affinity with inorganic materials. R represents an organic functional group that can react with polymers, such as vinyl, amino, epoxy, etc.
[0046] The process of modifying mica with a silane coupling agent used in the present invention is mainly divided into the following three parts:
[0047] In the first step, the silane coupling agent undergoes a hydrolysis reaction with a small amount of water additive, i.e., the X group is hydrolyzed to form silanol;
[0048] In the second step, the silanol groups are dehydrated and condensed into oligomers to generate silane oligomers;
[0049] In the third step, the silane oligomer forms a bond with the exposed hydroxyl groups on the surface of mica, and dehydrates to form a strong silicon-oxygen bond, i.e., -Si-OM- covalent bond (M is Si, Al, K, etc. in sericite). At the same time, the silanols between the molecules of the silane coupling agent associate with each other to form a mesh film covering the surface of the mica, making its surface organic. The specific coupling reaction is briefly described as follows: hydrolysis, condensation, and hydroxyl reaction.
[0050] The high hydrophobic cosmetic grade mica material of the present invention is successfully loaded on the surface of mica by the synergistic effect of multiple silane coupling agents, so that the silane coupling agent is prepared by loading the mica surface with high hydrophobic composite material. First, the ethoxy groups in the structures of three silane coupling agents, namely, γ-aminopropyl triethoxysilane (KH550), n-octyl triethoxysilane (OTES) and dodecyl triethoxysilane (DTES), are hydrolyzed to generate silanols under the action of an appropriate amount of water, and then silane oligomers are generated through dehydration condensation, and finally combined with -OH on the surface of mica to form hydrogen bonds or silicon oxygen bonds. Due to the large difference in the electronegativity of hydrogen and oxygen, the electron cloud is biased towards oxygen, so that the hydrogen atoms become semi-exposed protons and are easy to form hydrogen bonds with the silane oligomers. Partial covalent bonds are generated by heating dehydration reaction, and finally the mica surface is covered by KH550, OTES and / or DTES, and the linear alkyl functional groups of the silane coupling agent greatly improve the hydrophobicity of the mica surface.
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] 1. Using N,N-dimethylformamide, mica, KH550, OTES and / or DTES as raw materials, controlling the temperature, water usage and DMF usage, and allowing a variety of silane coupling agents to react with the hydroxyl groups on the surface of mica to successfully load the silane coupling agents on the surface of mica to synthesize highly hydrophobic cosmetic-grade mica materials; the cosmetic-grade mica material has good hydrophobicity, and the contact angle can reach up to 131°.
[0053] 2. The highly hydrophobic cosmetic-grade mica material of the present invention uses coupling agent KH550 as the main modifier, and is combined with OTES and / or DTES, that is, KH550+OTES, or KH550+OTES+DTES scheme is used for synergistic modification. The modified hydrophobic effect is significantly better than the hydrophobic effect of using one or two silane coupling agents alone; and the highly hydrophobic cosmetic-grade mica material has good softness and skin-fitting properties. Compared with unmodified mica, the mica material has high hydrophobicity, and can be effectively waterproof and sweat-proof when used in cosmetic products, which is conducive to the development of diversified functional cosmetics.
[0054] 3. When a silane coupling agent is used alone to modify mica materials on the market, the amount of silane coupling agent used is usually large; the highly hydrophobic cosmetic-grade mica material of the present invention uses coupling agent KH550 as the main modifier, and is synergistically modified with OTES and / or DTES, which not only greatly reduces the amount of silane coupling agent used, but also has a better hydrophobic effect than a single or other combination of silane coupling agents, which will be more conducive to industrial production and reduce production costs.
[0055] 4. The highly hydrophobic cosmetic-grade mica material of the present invention utilizes a variety of silane coupling agents to chemically combine with the hydroxyl groups on the surface of mica. DMF is used as a coupling reaction promoter to effectively improve the reaction efficiency of the silane coupling agent and mica. In addition, DMF can be recycled, and the modification effect can still achieve a high hydrophobic effect. The modification method of the present invention is not only simple and controllable, but also has a green and environmentally friendly synthesis scheme and good biocompatibility, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1a This is an infrared full spectrum detection diagram of the highly hydrophobic cosmetic-grade mica material obtained by the present invention.
[0057] Figure 1b The infrared spectrum of the highly hydrophobic cosmetic grade mica material obtained by the present invention is 3000-2500cm -1 Zoom in on the inspection image.
[0058] Figure 1c The infrared spectrum of the highly hydrophobic cosmetic grade mica material obtained by the present invention is 2000-1000cm -1 Zoom in on the inspection image.
[0059] Figure 2 1 is a graph showing the contact angle test results of the highly hydrophobic cosmetic grade mica material obtained in Example 1 and Example 2.
[0060] Figure 3 This is a contact angle test result diagram of the highly hydrophobic cosmetic grade mica material obtained in Example 3.
[0061] Figure 4 This is a contact angle test result diagram of the highly hydrophobic cosmetic grade mica material obtained in Example 4.
[0062] Figure 5 This is a contact angle test result diagram of the highly hydrophobic cosmetic grade mica material obtained in Example 5.
[0063] Figure 6 This is a contact angle test result diagram of the highly hydrophobic cosmetic grade mica material obtained in Example 6.
[0064] Figure 7 This is a contact angle test result diagram of the highly hydrophobic cosmetic grade mica material obtained in Example 7.
[0065] Figure 8 This is a contact angle test result diagram of the highly hydrophobic cosmetic grade mica material obtained in Example 8.
[0066] Fig. 9 1 is a graph showing the contact angle test results of the highly hydrophobic cosmetic grade mica material obtained in Example 9.
[0067] Fig.10 This is a graph showing the contact angle test results of the mica materials obtained in Comparative Examples 1 and 3.
[0068] Fig.11 This is a graph showing the contact angle test results of the mica materials obtained in Comparative Examples 5 and 6.
[0069] Fig.12 This is a SEM test image of the highly hydrophobic cosmetic-grade mica material prepared by the present invention. DETAILED DESCRIPTION
[0070] The following non-limiting examples can make those of ordinary skill in the art understand the present invention more comprehensively, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention according to the disclosed content, and it should also belong to the scope of the present invention. When the embodiment gives a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those of ordinary skill in the technical field to which the present invention belongs.
[0071] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.
[0072] In the following examples, the mica was purchased from Anhui Ge Rui New Material Technology Co., Ltd., with the product number GH-103;
[0073] The DMF (N,N-dimethylformamide) was purchased from Shanghai Jizhi Biochemical Technology Co., Ltd., with the product number N67024;
[0074] The KH550 (γ-aminopropyltriethoxysilane) was purchased from Shanghai Yuanye Biotechnology Co., Ltd., with the product number S15028;
[0075] The OTES (n-octyltriethoxysilane) was purchased from Guangzhou Weigu Technology Co., Ltd., with the product number T107262;
[0076] The DETS (dodecyltriethoxysilane) was purchased from Guangzhou Xiaofan Technology Co., Ltd. with the item number D834042.
[0077] For the above components, products from different manufacturers have no significant effect on the effects.
[0078] Example 1
[0079] (1) Disperse 10 g of mica in 35 mL of N,N-dimethylformamide (DMF) and stir to fully disperse the mica to obtain slurry A;
[0080] (2) γ-aminopropyltriethoxysilane (KH550), n-octyltriethoxysilane (OTES) and dodecyltriethoxysilane (DTES) with a total addition amount of 1.875 mL were dissolved in slurry A at a volume ratio of 1:1:1 (mL:mL:mL), and stirred to fully dissolve to obtain slurry B;
[0081] (3) condensing and reflux heating slurry B at 120° C. for 1.5 h;
[0082] (4) adding 25 mL of pure water to the slurry B of step (3), stirring to fully dissolve it, to obtain slurry C;
[0083] (5) condensing and reflux heating slurry C at 120° C. for 1.5 h to obtain slurry D;
[0084] (6) Slurry D was filtered to obtain a precipitate, which was washed three times with anhydrous ethanol and pure water respectively, and dried at 105° C. for 4 h to obtain a white powdery highly hydrophobic cosmetic grade mica material (AP / O / DSM).
[0085] Example 2
[0086] (1) Disperse 10 g of mica in 35 mL of N,N-dimethylformamide (DMF) and stir to fully disperse the mica to obtain slurry A;
[0087] (2) dissolving γ-aminopropyltriethoxysilane (KH550), n-octyltriethoxysilane (OTES) and dodecyltriethoxysilane (DTES) in a total amount of 0.0705 mL in a volume ratio of 1:1:1 (mL:mL:mL) in slurry A, stirring to fully dissolve, to obtain slurry B;
[0088] (3) condensing and reflux heating slurry B at 120° C. for 1.5 h;
[0089] (4) adding 12.5 mL of pure water to the slurry B of step (3), stirring to fully dissolve it, to obtain slurry C;
[0090] (5) condensing and reflux heating slurry C at 120° C. for 1.5 h to obtain slurry D;
[0091] (6) Slurry D was filtered to obtain a precipitate, which was washed three times with anhydrous ethanol and pure water respectively, and dried at 105° C. for 4 h to obtain a white powdery highly hydrophobic cosmetic grade mica material (AP / O / DSM).
[0092] Example 3
[0093] Different from Example 2, the heating time in step (3) and step (5) is different, specifically:
[0094] Example 3-1 Example 3-2 110℃ 130℃
[0095] The rest is the same as in Example 2.
[0096] Example 4
[0097] The difference from Example 2 is that the amount of the silane coupling agent mixture added in step (2) is different, as follows:
[0098] Example 4-1 Example 4-2 Example 4-3 Example 4-4 Embodiment 4-5 7.5mL 5mL 3.75mL 1.875mL 0.938mL
[0099] The rest is the same as in Example 2.
[0100] Example 5
[0101] Different from Example 2, the heating time in step (3) and step (5) is different, specifically:
[0102] Example 5-1: The heating time in step (3) and step (5) is 1 h;
[0103] Example 5-2: The heating time in step (3) and step (5) is 2 h;
[0104] The rest is the same as in Example 2.
[0105] Example 6
[0106] The difference from Example 2 is that the amount of pure water added in step (4) is different, as shown below:
[0107] Example 6-1 Example 6-2 Example 6-3 Example 6-4 Example 6-5 Example 6-6 0mL 1mL 5mL 7.5mL 10mL 40mL
[0108] The rest is the same as in Example 2.
[0109] Example 7
[0110] Different from Example 2, in the silane coupling agent mixture in step (2), the volume ratios of γ-aminopropyltriethoxysilane (KH550), n-octyltriethoxysilane (OTES) and dodecyltriethoxysilane (DTES) are different, specifically:
[0111] Example 7-1 Example 7-2 1:1.5:0.5 1:0.5:1.5
[0112] The rest is the same as in Example 2.
[0113] Example 8
[0114] Different from Example 2, in step (4), the volume amounts of water and DMF are different, specifically:
[0115]
[0116]
[0117] The rest is the same as in Example 2.
[0118] Example 9
[0119] Example 9-1: The difference from Example 2 is that the silane coupling agent mixture is a mixture (0.0705 mL) of γ-aminopropyltriethoxysilane (KH550) and n-octyltriethoxysilane (OTES), with a volume ratio of 1:2. The rest is the same as Example 2.
[0120] Example 9-2: The difference from Example 2 is that the silane coupling agent mixture is a mixture (0.0705 mL) of γ-aminopropyltriethoxysilane (KH550) and n-octyltriethoxysilane (OTES), with a volume ratio of 1:1. The rest is the same as Example 2.
[0121] Comparative Example 1
[0122] The difference from Example 2 is that the silane coupling agent mixture (0.0705 mL) is a mixture of γ-aminopropyltriethoxysilane (KH550) and dodecyltriethoxysilane (DTES) in a volume ratio of 1:1. The rest is the same as Example 2.
[0123] Comparative Example 2
[0124] The difference from Example 2 is that the silane coupling agent mixture (0.0705 mL) is a mixture of γ-aminopropyltriethoxysilane (KH550) and dodecyltriethoxysilane (DTES) in a volume ratio of 1:2. The rest is the same as Example 2.
[0125] Comparative Example 3
[0126] The difference from Example 2 is that in step (1), N,N-dimethylformamide (DMF) is replaced by 1,4-dioxane. The rest is the same as Example 2.
[0127] Depend on Fig.10 It can be seen that after DMF was replaced with 1,4-dioxane, the contact angle decreased from 131° to 13°. Therefore, when DMF was used in conjunction with the three silane coupling agents, it played the role of a coupling reaction promoter, which could effectively improve the reaction efficiency of the silane coupling agent and mica and enhance the hydrophobic properties of the mica surface.
[0128] Comparative Example 4
[0129] The difference from Example 2 is that the heating time in step (3) and step (5) is different, specifically: the heating time in step (3) and step (5) is 0.5 h. The rest is the same as Example 2.
[0130] Comparative Example 5
[0131] The difference from Example 2 is that the silane coupling agent is different. Instead of using a silane coupling agent mixture, only a single-component silane coupling agent is used, specifically as follows:
[0132] Comparative Example 5-1 Comparative Example 5-2 Comparative Example 5-3 Comparative Example 5-4 Silane coupling agent type Single KH550 Single OTES Single DTES Single KH560
[0133] The rest is the same as in Example 2.
[0134] from Fig.11 It can be seen that the contact angles of KH550, OTES, DTES or KH560 were significantly reduced when silane was used alone to couple the two.
[0135] Using a single KH560 modified mica, water drops onto the compressed mica and quickly wets the mica surface, with a contact angle of almost 0°.
[0136] Comparative Example 6
[0137] The difference from Example 2 is that the silane coupling agent is different, and KH550 is replaced by KH560 (purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number S15029), that is, 0.0705 mL of KH560, n-octyltriethoxysilane (OTES) and dodecyltriethoxysilane (DTES) are mixed in a volume ratio of 1:1:1 (mL:mL:mL).
[0138] The rest is the same as in Example 2.
[0139] When water drops onto the compressed mica, it quickly wets the mica surface and the contact angle is almost 0°.
[0140] Comparative Example 7
[0141] Different from Example 2, the ratio of the silane coupling agent is different, and the volume ratio of γ-aminopropyltriethoxysilane (KH550), n-octyltriethoxysilane (OTES) and dodecyltriethoxysilane (DTES) is 1:0.5:6.
[0142] The rest is the same as in Example 2.
[0143] Technical effect testing
[0144] 1. Infrared detection method: Take a small amount of powder sample and mix it with an appropriate amount of KBr powder and grind it. Use a YP-2 hydraulic tablet press to prepare the sample into a sheet standard sample with a diameter of 13 mm and a thickness of 1 mm. Then use an iCAN9 Fourier transform infrared spectrometer for detection.
[0145] The infrared detection results of Example 2 are shown in Figure 1a , Figure 1b , Figure 1c ,in Figure 1a is the full infrared spectrum, Figure 1b and Figure 1c This is a partial enlarged view of the full infrared spectrum.
[0146] Depend on Figure 1a As shown in the figure, the modified mica AP / O / DSM is at 3622cm -1 , 912cm -1 The peak at 688cm belongs to the absorption peak of Si-OH stretching vibration of mica. Compared with the unmodified mica M, the absorption peak intensity is significantly weakened, which indicates that the hydroxyl content on the surface of the modified mica is reduced. -1 The absorption peak of Si-O stretching vibration of mica is represented by 1012cm. Compared with the unmodified mica M, the absorption peak intensity is significantly enhanced. The reason is that -OH on the surface of mica reacts with the silane oligomer generated by the hydrolysis of the silane coupling agent to generate Si-O; 1012cm -1 and 826cm -1Represent the Si-O-Si antisymmetric stretching vibration absorption peak and symmetric stretching vibration absorption peak of mica, 530cm -1 and 464cm -1 Represents the bending vibration absorption peak of the Si-O-Si bond of mica. Compared with the unmodified mica M, the Si-O-Si absorption peak intensity is enhanced and the vibration absorption area is broadened after modification. This is because the Si-O-Si formed by the silane coupling agent and the mica surface overlaps with the Si-O-Si vibration absorption band in the mica; 748cm -1 Represents the Al-O-Si stretching vibration absorption peak of mica. Figure 1a The infrared image of Figure 1b It can be seen that compared with the unmodified mica M, the modified mica AP / O / DSM has a peak at 2923 cm -1 , 2853cm -1 The peak at 3 、-CH 2 The stretching vibration absorption peak of Figure 1a The infrared image of Figure 1c It can be seen that compared with the unmodified mica M, the modified mica AP / O / DSM has a peak at 1459 cm -1 The unique absorption peak of KH550 appeared at , which further indicated that the silane coupling agents KH550, OTES and DTES had been coated on the surface of mica powder to form chemical adsorption.
[0147] 2. Contact angle detection method: Weigh 0.3g of sample, use YP-2 hydraulic tablet press to press, maintain pressure at 20MPa for 5min, water drop size is 10μL, then use KJ.63-JJC-1 contact angle meter to measure, press three times respectively, and take the average value as the final value.
[0148] The test results are shown in Table 1 and Figure 2-Figure 11 .
[0149] Table 1
[0150]
[0151]
[0152] 3. SEM detection method: Take 0.01g of the ground sample and disperse it in 1mL of anhydrous ethanol. After ultrasonic treatment for 15min, drop the sample on a glass slide and dry it naturally. Then spray platinum for 100s and measure it using a JSM-7610FPlus field emission scanning electron microscope.
[0153] Depend on Fig.12It can be seen from the SEM images that the highly hydrophobic cosmetic-grade mica material prepared by the present invention has a flaky structure before and after the mica is modified, and the surface of the AP / O / DSM flaky structure is evenly covered with the silicone modifier.
[0154] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a highly hydrophobic cosmetic grade mica material, characterized in that: Includes steps: (1) dispersing mica in DMF to obtain a mica-containing slurry A; (2) Mixing a silane coupling agent mixture containing KH550 with slurry A to obtain slurry B after mixing evenly; the silane coupling agent mixture containing KH550 is a mixture of KH550, OTES and DTES, and the volume ratio of KH550:OTES+DTES is 0.5-1:0.5-2; The ratio of the mass of the mica to the volume of the silane coupling agent mixture is 10:0.705 g / mL; (3) condensing and reflux heating the slurry B; (4) mixing water with the slurry obtained in step (3) to obtain slurry C; the volume ratio of water to DMF is 12.5:35; (5) condensing and reflux-heating slurry C to obtain slurry D; In step (3) and step (5), the condensation reflux heating is reflux heating at 120° C. for 1-1.5 h; (6) Slurry D is filtered, and the obtained precipitate is washed and dried to obtain a highly hydrophobic cosmetic grade mica material.
2. The preparation method according to claim 1, characterized in that: In step (1), the solid-liquid ratio of mica to DMF is 8-12:30-45 g / mL.
3. The preparation method according to claim 2, in step (1), the solid-to-liquid ratio of mica to DMF is 10:35 g / mL.
4. The preparation method according to claim 1, characterized in that: In step (2), the volume ratio of KH550:OTES+DTES is 1:
2.
5. The preparation method according to claim 4, characterized in that: In step (2), the volume ratio of KH550:OTES:DTES is 1:1:
1.
6. The highly hydrophobic cosmetic grade mica material prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the highly hydrophobic cosmetic grade mica material according to claim 6 in the preparation of cosmetics.
Citation Information
Patent Citations
Organic matter coating method of mica powder used for cosmetics
CN107337943A
Preparation method of hydrophobic oleophilic cochineal red pearlescent pigment
CN109021619A
Hydrophobic oleophylic modified synthetic mica and preparation method thereof
CN104194415A
Amine silane surface modified micro crystal isinglass active filler and its preparation method
CN1752154A